Génesis y destino de dos manuscritos de Platón: de Bizancio al Escorial a través de la Biblioteca Vaticana. - Martínez Manzano, Teresa (Myrtia, 2021)
Basing on textual, palaeographic, codicological and historic evidence, this paper firstly examines the history of the Platonic manuscript Escur. Ψ I 1 since its making in Corfu by Demetrios Triboles in 1461-62 till its purchase by Antonio Agustín in the middle of the 16th century. The textual sources of this codex and the copying process are also analysed. The conclusion reached through the examination of inventories in the Vatican Library is that the manuscript belonged to that library till the Sack of Rome in 1527. Secondly, this paper proves that another Platonic codex kept in El Escorial, Escur. y I 13, comes as well from the Vatican Library, from where it disappeared on the occasion of the Sack, and was later purchased by Juan Páez de Castro. Additionally, an attempt is made to prove that both Escur. Ψ I 1 and Escur. y I 13 belonged to the Vatican Library as early as 1475.